Melek Zaman, Bergerak Mapan: The Dynamics of Socioeconomic Change in Cirendeu within the Framework of Pasundan Cultural Resilience - M. Raihan Ardiansyah; Mochamad Arif Rahman; Rahmayanti Nur Malika; Bella Carolina Hutasoit; Guntur Bayu Julianto; Aditya Firmansyah; Nenden Siti Khodijah (Journal of Literary and Linguistic Research, 2026)
Cirendeu Traditional Village in Leuwigajah Subdistrict, Cimahi City, represents a distinctive indigenous community situated within the rapidly urbanizing Bandung Metropolitan Area. This study aims to analyze the dynamics of socioeconomic change in Cirendeu and examine how Pasundan cultural resilience functions as an adaptive framework for responding to modernization. The research employed a qualitative descriptive approach with an ethnographic design. Data were collected through participant observation, in-depth interviews, and documentary analysis. The findings indicate a transition from a subsistence-based agrarian economy toward diversified economic activities, including cassava-based creative industries, cultural tourism, entrepreneurship, and digital economic practices. Despite these transformations, the community continues to preserve Sundanese values, customary institutions, local ecological knowledge, and the principles of Sunda Wiwitan. Cultural resilience operates through selective adaptation, enabling community members to engage with technological innovation, formal education, and market expansion while maintaining cultural continuity. The concept of Melek Zaman, Bergerak Mapan reflects an adaptive form of modernity in which economic progress, social mobility, and cultural preservation coexist. The study highlights the strategic role of cultural resources in supporting sustainable community development amid accelerating urban and socioeconomic change.